Quantifying the CO₂ mitigation potential from sustainable urban planning in European cities - Peter Berrill; Florian Nachtigall; Felix Creutzig (Sustainable Production and Consumption, 2026)

Measuring the impact of urban morphology on residential energy consumption at the neighborhood-level in the Netherlands - Han Yu; Mingming Hu; Arnold Tukker; Peter Berrill (Sustainable Cities and Society, 2026)

Towards an integrated understanding of circularity, urban design, planetary stability and well-being - Mira Kopp; Peter Berrill; Harald Desing; Aneeque Javaid; Alessio Mastrucci; Nikola Milojevic-Dupont; Florian Nachtigall; Jakob Napiontek; Hauke Schlesier; Mafalda Silva; Dominik Wiedenhofer; Charlie Wilson; et al. (Journal of Industrial Ecology, 2026)
Circularity strategies are increasingly recognized as essential for reducing greenhouse gas (GHG) emissions and improving material efficiency in urban environments. However, existing approaches often analyze sectors in isolation, limiting their ability to capture systemic interactions and spatial dependencies. In this study, we introduce the Integrated Urban Circularity (INTURC) framework that integrates construction, building energy use, transport infrastructure, waste management, and overarching urban planning strategies to guide consistent modelling efforts. INTURC enables the explicit identification of both cross-sectoral circularity policies, which generate synergistic effects across multiple urban systems, as well as domain-specific interventions with more localized impacts. In contrast to established circularity modelling, we suggest capturing the spatial relationships in context of the social setting and policy designs that shape circularity outcomes, such as destination accessibility, information feedback and infrastructure reuse. By embedding circularity strategies within institutional and urban design contexts, INTURC facilitates systemic assessments that support effective policy prioritization.

Assessing the social acceptability of sufficiency measures in the residential sector - Konstantin Arndt; Peter Berrill; Sabine Fuss (Journal of Industrial Ecology, 2026)
Efficiency measures are insufficient for achieving greenhouse gas neutrality in the residential sector. Additional efforts are needed, with the concept of sufficiency gaining increasing attention. Sufficiency targets demand side and behavioural change, while delivering wellbeing. Reducing living space per capita is a sufficiency measure often suggested for residential buildings. However, research dealing with social perceptions and attitudes towards sufficiency is limited. We conducted a survey of Berlin households to assess correlates of current living space, and examine satisfaction with current living space and willingness to downsize. A large proportion of the population is willing to reduce their living space, 43% of survey participants could envisage downsizing without compromising their personal wellbeing. Older people (aged 66–80) have the highest per capita consumption of living space of all age groups and are attracted to new living models, such as cluster apartments, as these models strengthen social interaction and promote autonomy. Empty-nesters also show high sufficiency potential, over half of this group indicate willingness to reduce living space. The paper highlights group-specific sufficiency potential and provides policymakers with suggestions for developing strategies that support downsizing while preserving or improving the wellbeing of residents.

Socio-ecological inequalities in housing consumption: How income, urban form, and tenure drive carbon footprints - Federico Savini; Mira Kopp; Cody Hochstenbach; Leshem Cohen; Peter Berrill; Stefano Merciai (Ecological Economics, 2026)

Material circularity strategies in the stock-flow-service nexus of buildings, transport, electricity, machinery, furniture, and appliances - Martijn van Engelenburg; Peter Berrill; Paul Behrens; Sebastiaan Deetman; Tomer Fishman; Stefan Pauliuk; Christian Hauenstein; Edgar Hertwich; Meng Jiang; Oreane Edelenbosch; Marianne Zanon Zotin; Luja von Köckritz; et al. (Journal of Industrial Ecology, 2026)
Increasing global population and rising levels of wealth are raising demands for services such as shelter and mobility, leading to greater resource use and environmental impacts. Circular strategies can reduce the resources required for these services. However, the potential of circular strategies to reduce material demand is rarely quantified. Here, we present a method to link service, product, and resource use with circular material reduction strategies. We estimate the potential material reductions for shelter, mobility (including transportation infrastructure), spatial and thermal comfort, and supporting assets such as machinery, and energy infrastructure. We provide a review of the current state of the art on circularity strategies and stock-flow-service (SFS) data availability for the sectors of shelter, mobility (including transportation infrastructure), comfort, and supporting assets such as machinery, and energy infrastructure. We then make a first-order assessment of their theoretical potential for primary material demand reductions by linking them in a counterfactual approach. These show that the current global service provision and supporting assets rely on an in-use material stock of 81 tons per person, with 1.2 ton of materials needed per capita and year to maintain this stock. Current circular strategies could reduce primary material flows by 68% in the absence of rebound effects, economic, policy, or behavioral implications. 15% reduction would be achieved through modal shifts and sharing of products, 31% by slowing the resource flows via longer product lifetimes, and 22% by reusing and recycling materials. This analysis and extensive data repository serve as a starting point for more detailed multi-sector future projections.

Mapping material stocks in Pakistan’s built environment: Rethinking the definition of house across socio-economic contexts - Shiza Aslam; Peter Berrill; Tomer Fishman (Journal of Industrial Ecology, 2026)
Building material stocks (MS) account for over half of global raw material demand, significantly contributing to carbon emissions and land-use change. Yet, most research on material use in built environments focuses on Global North, overlooking rapidly urbanizing Global South. In this study, we present first spatially resolved estimates of building MS for three distinct socio-economic contexts in Pakistan. We develop a bottom-up framework that integrates census data with Google Open Buildings, Humanitarian OpenStreetMap, and World Settlement Footprint building heights data to classify building stocks by structural type. We derive material intensity (MI) through expert surveys, field measurements, local carpenters’ interviews, and bills of quantity. We quantify MIs of seven major construction materials across seven building archetypes. The estimated material stock is 616,328 kt for Karachi, 9,084 Kt for Hyderabad, and 46 kt for Deh 294. For pacca (permeant) buildings, in Karachi, we observe variation in MIs between high and low-income neighborhoods. To address lack of household-level socioeconomic data, we estimate MS in Karachi using a range-based approach, from 215,360 kt (low-income scenario) to 616,328 kt (high-income scenario). Our approach distinguishes rural settings, where multifunctional plots and semi-built spaces like verandas complicate standard floor area measures and house definition. By disaggregating MIs into sheltered and fenced areas, we reveal substantial variation: Semi-Pacca shows 1,759 kg/m 2 over a total area of 1,633 kg/m 2 , while Katcha shows 469 kg/m 2 over 258 kg/m 2 . Our mixed-methods approach captures urban–rural building diversity and provides a transferable framework for MS accounting in under-documented Global South contexts.

BUD-MI: a template that optimizes material intensity data collection and utilization - Maud Lanau; Charles Gillott; Will Mihkelson; Kimberlee Zamora; Peter Berrill; Niko Heeren; Georg Schiller; Ruichang Mao; Mohit Arora; Karin Gruhler; Gang Liu; Hiroki Tanikawa; et al. (Journal of Industrial Ecology, 2026)
Mapping construction material stocks is essential for understanding socioeconomic metabolism and informing the circular economy. However, spatial material stock studies often produce coarse results owing to challenges in material intensity development. This paper introduces BUD-MI (Bottom-Up Data: Material Intensity), a material intensity data collection template designed with three core objectives: streamlining the data collection process during building sampling, supporting cumulative research while ensuring project-specific relevance, and enhancing the utility of results for the construction industry. BUD-MI aims to assist researchers, students, and construction practitioners in developing material intensity data in line with these three objectives. The development process required identifying material intensity challenges, eliciting requirements, mapping relevant domain work and creating missing ones, and assembling them all into BUD-MI. The template consists of three data input tabs, two mini-tools for data input assistance, four result generation tabs, and additional tabs for background data and ancillary information. A case study in Sheffield, UK, illustrates BUD-MI’s functionalities, enabling bespoke material intensity results to be disaggregated across building elements and components. BUD-MI supports future material intensity data collection efforts, ensuring data quality, granularity, comparability, transferability, and availability, thereby advancing socioeconomic metabolism and circular economy research and practice.

Quantifying material stocks in long-lived products: Challenges and improvements for informing sustainable resource use strategies - Jan Streeck; André Baumgart; Helmut Haberl; Fridolin Krausmann; Bowen Cai; Tomer Fishman; Maud Lanau; Peter Berrill; Zhi Cao; Sebastiaan Deetman; David Frantz; Volker Krey; et al. (Resources, Conservation and Recycling, 2025)

Built environment and travel: Tackling non-linear residential self-selection with double machine learning - Florian Nachtigall; Felix Wagner; Peter Berrill; Felix Creutzig (Transportation Research Part D: Transport and Environment, 2025)

Comparing urban form influences on travel distance, car ownership, and mode choice - Peter Berrill; Florian Nachtigall; Aneeque Javaid; Nikola Milojevic-Dupont; Felix Wagner; Felix Creutzig (Transportation Research Part D: Transport and Environment, 2024)

A comprehensive set of global scenarios of housing, mobility, and material efficiency for material cycles and energy systems modeling - Tomer Fishman; Niko Heeren; Stefan Pauliuk; Peter Berrill; Qingshi Tu; Paul Wolfram; Edgar G. Hertwich (Journal of Industrial Ecology, 2021)

Linking service provision to material cycles: A new framework for studying the resource efficiency–climate change (RECC) nexus - Stefan Pauliuk; Tomer Fishman; Niko Heeren; Peter Berrill; Qingshi Tu; Paul Wolfram; Edgar G. Hertwich (Journal of Industrial Ecology, 2021)
Material production accounts for 23% of all greenhouse gas emissions. More efficient use of materials—through decoupling of services that support human well‐being from material use—is imperative as other emission mitigation options are expensive. An interdisciplinary scientific assessment of material efficiency and its links to service provision, material cycle management, and climate policy is needed to identify effective strategies and help design the policy framework required for their implementation. We present the resource efficiency–climate change (RECC) mitigation framework, a first step toward such a comprehensive assessment. RECC is based on dynamic material flow analysis and links the services provided (individual motorized transport and shelter) to the operation of in‐use stocks of products (passenger vehicles and residential buildings), to their expansion and maintenance, and to their material cycles to model mitigation strategies and analyze trade‐offs for environmental impacts along the products’ life cycle. A key innovation of RECC is the upscaling of product archetypes with different degrees of material and energy efficiency, which are simulated with engineering tools. We utilize RECC with augmented storylines of the shared socioeconomic pathways to describe future service demand and associated material requirements. Ten material efficiency strategies at different stages of the material cycle can be assessed by ramping up their implementation rates to the identified technical potentials. RECC provides scenario results for the life cycle impacts of ambitious service–material decoupling concurrent with energy system decarbonization, giving detailed insights on the RECC mitigation nexus to policy‐makers worldwide.

Capital in the American carbon, energy, and material footprint - Peter Berrill; T. Reed Miller; Yasushi Kondo; Edgar G. Hertwich (Journal of Industrial Ecology, 2020)

Method for endogenizing capital in the United States Environmentally‐Extended Input‐Output model - T. Reed Miller; Peter Berrill; Paul Wolfram; Ranran Wang; Yookyung Kim; Xinzhu Zheng; Edgar G. Hertwich (Journal of Industrial Ecology, 2019)
Each year businesses, governments, and homeowners in the United States invest around one fifth of gross domestic product into the creation of capital assets such as buildings, machinery, and software to enable production and consumption. Use of capital is typically included to some extent in environmental life cycle assessments of goods and services but is not incorporated into most environmentally extended input‐output (EEIO) models, including the US Environmental Protection Agency's USEEIO. Capital assets are typically created in years prior to their use, so a challenge lies in distributing the impacts of their creation over time. In this work, a highly detailed capital flow matrix approach is followed to distribute the use of fixed capital assets to consuming industries. Data from the US Bureau of Economic Analysis's Fixed Asset Accounts is merged with its Industry Accounts data by the creation of concordance tables. Public highways and streets are partially reallocated to industries operating vehicles. The resulting capital use matrix is later combined into a modified USEEIO. “Housing” is found to be the largest consumer of fixed assets, followed by general government, fossil fuel extraction, and financial industries involved in leasing. Construction, vehicles, and machinery are mostly used by industries in the form of fixed assets. The types of fixed assets used by industries are consistent with expectations: housing is dominated by structures, transport by equipment, and information industries by intellectual property products.

New predictive equations for Arias intensity from crustal earthquakes in New Zealand - Peter J. Stafford; John B. Berrill; Jarg R. Pettinga (Journal of Seismology, 2009)

Seismic source identification and characterisation for probabilistic seismic hazard analyses conducted in the Buller–NW Nelson Region, South Island, New Zealand - Peter J. Stafford; Jarg R. Pettinga; John B. Berrill (Journal of Seismology, 2008)